Bulk and surface electronic structure of NiO and CoO: a comparative ab initio LSDA+U analysis and application to the interpretation of STM images - Dudarev, S; Castell, M; Briggs, G; Sutton, A (1999)
Atomically resolved scanning tunneling microscope images of (001) cobalt and nickel monoxide surfaces are interpreted on the basis of LSDA + U surface electronic structure calculations. Different symmetry of dangling unoccupied d-bonds on CoO(0 0 1) and NiO(0 0 1) explains the origin of an order of magnitude difference in the contrast of tunnelling images observed for the two surfaces. (C) 1999 Elsevier Science B.V. All rights reserved.